2020
DOI: 10.1371/journal.pbio.3000679
|View full text |Cite
|
Sign up to set email alerts
|

Acute inhibition of centriolar satellite function and positioning reveals their functions at the primary cilium

Abstract: Centriolar satellites are dynamic, membraneless granules composed of over 200 proteins. They store, modify, and traffic centrosome and primary cilium proteins, and help to regulate both the biogenesis and some functions of centrosomes and cilium. In most cell types, satellites cluster around the perinuclear centrosome, but their integrity and cellular distribution are dynamically remodeled in response to different stimuli, such as cell cycle cues. Dissecting the specific and temporal functions and mechanisms o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…In agreement with previous reports, PCM1 depletion resulted in a significant decrease in the percentage of ciliated cells relative to control cells and the cilia that formed in these cells were significantly shorter ( Fig. 7B,C ) (siControl: 79.80 ± 6.14%, siPCM1: 31.97 ± 2.79%, p<0.001; siControl: 5.33μm ± 0.14μm; siPCM1:3.89 μm ± 0.15 μm, p<0.0001) (Aydin et al, 2020, Kim et al, 2008, Stowe et al, 2012. While MLN8237-and DMSO-treated cells ciliated with similar efficiencies (p>0.1), AURKA inhibition partially restored the ciliogenesis defect in PCM1-depleted cells (siPCM1+DMSO: 31.97 ± 2.79%; siPCM1+MLN8237: 49.70 ± 2.14%, p<0.01; siControl+DMSO: 79.80 ± 6.14%, siControl+MLN8237: 49.70 ± 7.6%, p=0.94) ( Fig 7C).…”
Section: Centriolar Satellites and Aurka Have Antagonistic Functions supporting
confidence: 65%
See 2 more Smart Citations
“…In agreement with previous reports, PCM1 depletion resulted in a significant decrease in the percentage of ciliated cells relative to control cells and the cilia that formed in these cells were significantly shorter ( Fig. 7B,C ) (siControl: 79.80 ± 6.14%, siPCM1: 31.97 ± 2.79%, p<0.001; siControl: 5.33μm ± 0.14μm; siPCM1:3.89 μm ± 0.15 μm, p<0.0001) (Aydin et al, 2020, Kim et al, 2008, Stowe et al, 2012. While MLN8237-and DMSO-treated cells ciliated with similar efficiencies (p>0.1), AURKA inhibition partially restored the ciliogenesis defect in PCM1-depleted cells (siPCM1+DMSO: 31.97 ± 2.79%; siPCM1+MLN8237: 49.70 ± 2.14%, p<0.01; siControl+DMSO: 79.80 ± 6.14%, siControl+MLN8237: 49.70 ± 7.6%, p=0.94) ( Fig 7C).…”
Section: Centriolar Satellites and Aurka Have Antagonistic Functions supporting
confidence: 65%
“…Having established the link between satellites and AURKA regulation in quiescent cells, we next investigated the functional consequences of this regulatory relationship. Recent studies showed that satellites function as trafficking and storage sites for key ciliogenesis factors and regulate primary cilium assembly, maintenance and disassembly (Aydin et al, 2020, Odabasi et al, 2019, Wang et al, 2016). However, the proteins regulated by satellites during cilium biogenesis have not been fully characterized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These lines of evidence confirm the tight regulatory and functional relationship of satellites with centrosomes and cilia. Consistently, satellites have emerged as key regulators of cilium assembly and maintenance, Hedgehog signaling and mitotic progression [ 3 , 85 , 86 , 87 ]. Recent studies aimed at dissecting satellite composition, dynamics and functions have unraveled regulation of centrosomal and ciliary protein abundance as the major mechanism by which satellites mediate their functions [ 2 , 3 ].…”
Section: Structure Of the Mammalian Centrosome/cilium Complexmentioning
confidence: 99%
“…Upon mitotic exit, DYRK3 is degraded following its APC/C-mediated ubiquitination and thereby satellites reassemble and cluster around centrosomes [ 89 ]. Although the functional significance of the mitotic dissolution of satellites is not known, recent studies suggest that it might contribute to satellite functions during mitotic progression [ 85 ]. Future studies are required to elucidate the mechanisms that regulate satellite assembly, remodeling and disassembly as well as their number control.…”
Section: Structure Of the Mammalian Centrosome/cilium Complexmentioning
confidence: 99%